Burden of hypertensive heart disease among women of childbearing age in global, regional, and national regions from 1990 to 2021 and projection until 2040 - Wang, Zhenglong; Li, Hao; Wei, Hongwei; Liu, Baotang; Li, Lei; Li, Zijun; Feng, Jindong; Hu, Yunjie; Liu, Xiaobo (Frontiers in Global Women's Health, 2025)
BackgroundThe present research focuses on elucidating the global burden of hypertensive heart disease (HHD) among women of childbearing age (WCBA). By utilizing all available data and adopting the methodology employed in the Global Burden of Disease (GBD) study, this study aims to comprehensively analyze the epidemiological characteristics of this highly prevalent disorder.MethodsIn this research, we retrieved three key indicators—prevalence, incidence, and DALYs—related to HHD in WCBA from the GBD database for the period 1990 to 2021. Our study provides point estimates along with their corresponding 95% uncertainty intervals (UIs). The evolving trends were assessed using the EAPC and percentage change.ResultsIn 2021, the global prevalence of HHD among WCBA was 544,544 cases, resulting in 25,669 deaths. Compared to 1990, the prevalence increased by 110%, and mortality rose by 27%. From 1990 to 2021, the prevalence rate showed an upward trend (EAPC: 1.31), whereas the mortality rate exhibited a decline (EAPC: −0.51). In 2021, middle SDI regions recorded the highest prevalence rate (30.88 per 100,000), while low SDI regions had the highest mortality rate (2.44 per 100,000) and the greatest burden of DALYs (125.39 per 100,000). Among different age groups in 2021, the 45–49 age group experienced the highest number of cases (195,288) and the highest prevalence rate (82.87 per 100,000). Furthermore, HHD prevalence demonstrated a positive correlation with age.ConclusionOverall, on a global scale, the burden of HHD among WCBA has significantly increased over the past 32 years. This trend is particularly pronounced in low SDI regions and within the 45–49 age group. The findings of this study highlight the critical need for targeted interventions to address this issue.